2018
DOI: 10.1080/01459740.2017.1417278
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Navigations and Social Networking: Mozambican Women’s Quests for Fertility

Abstract: In Mozambique, involuntary childlessness triggers immediate treatment seeking, especially on the woman's side. Treatment processes involve the activation and/or creation of situational social networks that provide emotional, instrumental, and informational support. These are formed through careful processes of disclosure management, and are embedded in social relations and local moral configurations of family making, reproduction, and healing. In this article I explore social networks involving friends, family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Very much like my respondents' therapeutic quests, I found that my fi eldwork process was also one of social navigation and situational social networks (Faria 2018;Vigh 2009). It is about trying to make the best of the opportunities that appear and manoeuvring through obstacles.…”
Section: Navigating Maputo: Plans and Changementioning
confidence: 96%
See 1 more Smart Citation
“…Very much like my respondents' therapeutic quests, I found that my fi eldwork process was also one of social navigation and situational social networks (Faria 2018;Vigh 2009). It is about trying to make the best of the opportunities that appear and manoeuvring through obstacles.…”
Section: Navigating Maputo: Plans and Changementioning
confidence: 96%
“…In this article, I look at the pragmatics of the fi eldwork process with a focus on my own personal experience. Rather than an analytical piece, as I have developed elsewhere (Faria 2018), I opt here for a more descriptive and informal tone. I argue for the relevance of fl exibility and refl exivity in fi eldwork and analytical practice, but also -following authors such as Hansjörg Dilger and colleagues (2015) for the specifi c case of medical anthropology -for the relevance of the notion that ethnographers are in a privileged position to explore, and go beyond, the crystallised division between context, the private fi eldwork experience of the researcher, and the published text of the scientist (Latour 1993).…”
mentioning
confidence: 99%
“…Sources of support vary widely for those experiencing infertility and may include family members, friends, peers similarly affected by infertility, acquaintances, mental health professionals, medical staff and faith-based institutions (Bell, 2012;Faria, 2018;Papadatou et al, 2016;Yager et al, 2010). Even social media networks have been noted as a source of support for people considering ART (Fisher, 2013;Gezinski et al, 2018).…”
Section: Sources Of Supportmentioning
confidence: 99%
“…Nor did they receive support from their homophobic family members. Mozambican women using ART reported instability in their relationships with husbands and in-laws (Faria, 2018). Fear of criticism was associated with selective disclosure of assisted reproduction (Bell, 2012;Gezinski et al, 2018), which may exacerbate feelings of social isolation and mental distress.…”
Section: Sources Of Supportmentioning
confidence: 99%
“…Women often were required to travel for IVF treatment and during these travels or in clinic waiting rooms, women helped each other cope emotionally with and provide information about possible treatments. These connections often served as temporary networks that dissolve once women conceive (Faria 2018).…”
Section: Agency Socialities and Narrativesmentioning
confidence: 99%